Implikasi Peraturan Pemerintah Nomor 37 Tahun 2021 Tentang Penyelenggaraan Program Jaminan Kehilangan Pekerjaan Terhadap Pemberi Kerja Dan Pekerja - Suparto, Suparto; Admiral, Admiral; Susilo, Efendi Ibnu (Lex Librum : Jurnal Ilmu Hukum, 2024)
Government Regulation Number 37 of 2021 on the Implementation of the Job Loss Guarantee Program provides adequate legal protection for workers who lose their jobs, in addition to providing a sense of social security to former workers. It is also in accordance with the mandate of Article 28D of the 1945 Constitution of the Republic of Indonesia, which shows that the state is present in providing legal protection related to severance pay through the job loss guarantee so that workers affected by the termination of employment are still protected for a certain period while they search for new jobs. Because job loss insurance is very important, especially during the pandemic, it is a very good social security measure in Indonesia. Job loss insurance must be implemented properly and continuously monitored to ensure its objectives are achieved without causing problems in the future, and it needs to be socialized to employers and workers. Government Regulation Number 37 of 2021 on the Implementation of the Job Loss Guarantee Program is the government's effort to improve the welfare of the people, especially workers in Indonesia, with the aim of achieving social welfare. The job loss guarantee scheme can help former employees find new jobs more quickly and prevent them from losing the desire to seek new employment.